Delaying chloroplast turnover increases water-deficit stress tolerance through the enhancement of nitrogen assimilation in rice. (27th July 2017) - Sade, Nir; Umnajkitikorn, Kamolchanok; Rubio Wilhelmi, Maria del Mar; Wright, Matthew; Wang, Songhu; Blumwald, Eduardo
Abstract : Silencing of the CHLOROPLAST VESICULATION gene leads to plant stress tolerance and increased nitrogen assimilation in rice. Abstract: Abiotic stress-induced senescence in crops is a process particularly affecting the photosynthetic apparatus, decreasing photosynthetic activity and inducing chloroplast degradation. A pathway for stress-induced chloroplast degradation that involves the CHLOROPLAST VESICULATION ( CV ) gene was characterized in rice ( Oryza sativa ) plants. OsCV expression was up-regulated with the age of the plants and when plants were exposed to water-deficit conditions. The down-regulation of OsCV expression contributed to the maintenance of the chloroplast integrity under stress. OsCV -silenced plants displayed enhanced source fitness (i.e. carbon and nitrogen assimilation) and photorespiration, leading to water-deficit stress tolerance. Co-immunoprecipitation, intracellular co-localization, and bimolecular fluorescence demonstrated the in vivo interaction between OsCV and chloroplastic glutamine synthetase (OsGS2), affecting source–sink relationships of the plants under stress. Our results would indicate that the OsCV-mediated chloroplast degradation pathway is involved in the regulation of nitrogen assimilation during stress-induced plant senescence.